DESIGN AND DEVELOPMENT OF A SOLAR COOKER - MUHAMMAD KHAIRIL ANUAR BIN MOKHTAR, MUHAMMAD KHAIRIL (Universiti Teknologi PETRONAS, 2008)
Solar cooker is popular in developing country such as Africa and India since most of the regions received more heat by solar radiation from the sun. The main focus of the project is to design and development of a solar cooker for cooking and determine the best materials for the insulation. The project is proceed with the experiment to find the lowest thermal conductivity of selected materials followed by calculation of insulation thickness. The material for the solar cooker is chosen based on the several criteria such as material properties, locally available, and cost. After the fabrication of the solar cooker is done, the stagnation test is carried to monitor and record the solar cooker performance by measure the temperatures inside the cooking chamber. Through the experiment and calculations, the value of thermal conductivity of selected insulation is determined. The thickness of the rice straw and glass fiber for the solar cooker is 26.76 mm and 28.9 mm respectively to achieve 100 ºC on the absorber plate. Results of thermal performance test for the absorber plate average temperatures from 12 pm to 1 pm is 120.9 ºC and 102.3 ºC by using rice straw and glass fiber insulation in place respectively. The thermal conductivity of rice straw by experimentally is 7.97% less than glass fiber. The efficiency of the solar cooker by using rice straw is increased 12.7 % compared to glass fiber as insulation. The performance of the cooker with rice straw as insulation was improved compared to the glass fiber.